Seagrass Gains: Faster Growth, Better Condition, Less Effort for Juvenile Snapper ( Chrysophrys auratus ) - Jessica L. Campbell; Christine Stewart; Mark A. Morrison (New Zealand Journal of Marine and Freshwater Research, 2026)
Seagrass habitats are widely recognised as key nursery areas for juvenile fish, yet their specific role in supporting growth and condition remains incompletely understood. This study investigates the diet, growth and condition of juvenile (0+) snapper ( Chrysophrys auratus ) across multiple habitats in the Hauraki Gulf and northeastern New Zealand, with a focus on seagrass meadows. A total of 416 snapper were analysed for condition and growth, while diet composition was assessed from 425 gut samples. Results indicate that snapper within seagrass habitats exhibited significantly higher condition and faster growth rates than those in other habitats. However, contrary to expectations, gut fullness was lower in seagrass beds than in non‐seagrass habitats, despite higher prey availability in seagrass meadows. While diet varied among habitat types, no significant differences were detected between seagrass and non‐seagrass habitats. These findings suggest that the advantages conferred by seagrass are not directly linked to food intake but may result from reduced energetic costs associated with shelter from currents, improved foraging efficiency, or lower predation stress. The study highlights the vital role of seagrass meadows in supporting juvenile snapper populations and emphasises the need for conservation and restoration, particularly in areas where these habitats have been lost.